5x+2+9x-3=90

Simple and best practice solution for 5x+2+9x-3=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+2+9x-3=90 equation:


Simplifying
5x + 2 + 9x + -3 = 90

Reorder the terms:
2 + -3 + 5x + 9x = 90

Combine like terms: 2 + -3 = -1
-1 + 5x + 9x = 90

Combine like terms: 5x + 9x = 14x
-1 + 14x = 90

Solving
-1 + 14x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 14x = 90 + 1

Combine like terms: -1 + 1 = 0
0 + 14x = 90 + 1
14x = 90 + 1

Combine like terms: 90 + 1 = 91
14x = 91

Divide each side by '14'.
x = 6.5

Simplifying
x = 6.5

See similar equations:

| 5+m=3-m | | 800+50x=16 | | x^2-9x+68=0 | | 3x+(-2-4)= | | H(h)=-16t^2+96t+4 | | -6-(-x)=-7 | | g(x)=-5x^3-6x^2+7x-7 | | .75(t^2+1)=(t^2-t+1) | | (5x^2-3x)-(2x^2-7x)+(5x^2-6)=a | | 3v-8=-5 | | 3u^2-7u+60=0 | | x(7-x)+9x=-4 | | -8X+5X=21 | | 8x+13y=-68 | | (b+4)2b^2+8b+0=0 | | M=J+Jrt | | 2b^2+8b+0=0 | | 3w^2+13w+21=0 | | 2w^2+11w+19+w^2+2w+2=0 | | -(x+2)+3x=-12 | | g(x)=x^3+5x^2-4x-2 | | (-9+3n^6+3n^5)+(2n^6+5n^5+6)=x | | 3d^3-6d^2=24d | | 12-2.4n=2.4 | | 5.2+0.5q=6 | | 4x^2-8=16 | | 8x+20=3x+56 | | 8x+20=-3x+56 | | 48+36=x | | 8-5(3x-2)=15x+18 | | 46+6h=160 | | 21x+2+14x+3=180 |

Equations solver categories